2018
DOI: 10.1111/cdoe.12436
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in South American Indigenous peoples: A systematic review

Abstract: Objectives To determine the severity of dental caries in South American Indigenous peoples. Methods A systematic review was conducted regarding the severity of dental caries in South American Indigenous peoples using the following electronic databases: MEDLINE/PubMed, SCOPUS, SciELO, LILACS and grey literature up to March 2018. Literature search was conducted up to March 2018. No restrictions on language or year of publication were applied. Descriptive analysis and meta‐analysis of studies were performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The tooth develops immediately after the last primary tooth at the age of six and is most likely to be decayed. The American Academy of Pediatric Dentistry, the American Dental Association, and the American Academy of General Dentistry all recommend making sure to see a dentist 6 months after the eruption of teeth in children, before the age of one year's [161][162][163][164][165][166]. One of the most important and available measures to prevent caries, especially primary teeth in children, is performing dental procedures such as fissure sealant and fluoride therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The tooth develops immediately after the last primary tooth at the age of six and is most likely to be decayed. The American Academy of Pediatric Dentistry, the American Dental Association, and the American Academy of General Dentistry all recommend making sure to see a dentist 6 months after the eruption of teeth in children, before the age of one year's [161][162][163][164][165][166]. One of the most important and available measures to prevent caries, especially primary teeth in children, is performing dental procedures such as fissure sealant and fluoride therapy.…”
Section: Discussionmentioning
confidence: 99%
“…12 The clinical examinations were performed in households by a team of dentists who had been previously trained and calibrated. The survey in the Indigenous population was carried out by a team of 26 dentists who worked in the Indigenous Health Care Subsystem (SASI-SUS) that is linked to the Nacional Unified Health The Indigenous oral health survey study protocol (Number 16,632)…”
Section: Me Thodmentioning
confidence: 99%
“…The diversity of socio-historical, environmental, economic and ethnic contexts in which the interaction between Indigenous and non-Indigenous persons has occurred could determine a variety of protective and risk factors related to oral health that would impact differently on the health of each individual Indigenous group. 15,16 Evidence suggests that the oral health transition among Indigenous groups is a dynamic process, and unfavourable situations can be minimized and even reversed through well-structured health programmes appropriate to Indigenous reality. 6,15,17,18 In Brazil, the Xavante case illustrates this process well.…”
Section: Contact Between Indigenous and Non-indigenous Persons Inmentioning
confidence: 99%
“…26 Several studies conducted in Latin American indigenous people have shown a rise in the caries prevalence and severity, 45 with a systematic review concluding that sex-based differences and increasing age were associated with a higher caries experience in Guarani and Xavanti groups in Brazil. 59 With respect to the parents' low educational level, an association was found with higher caries prevalence in cross-sectional studies conducted in Colombia, 60 Mexico, 61 and Chile. 62 Further, low socioeconomic status was associated with a higher prevalence of dental caries.…”
Section: Socioeconomic and Demographic Factors In Laccmentioning
confidence: 95%